A teamwork framework for preventing breaches of academic integrity and improving students’ collaborative skills in the AI era - Issa, Tomayess; Hall, Mahnaz (Elsevier, 2024)
Generative artificial intelligence (AI) tools have become a major challenge in the education sector in terms of the way that students use and manage them. This study examines the development, implementation, and evaluation of a teamwork framework by using academic integrity standards and formative feedback to minimise the use of generative AI tools in the Business Project Management (BPM) unit and promote students' learning skills through teamwork and self/peer evaluation. This teamwork assessment was designed to transform students into independent learners by improving their cultural awareness, self-confidence, teamwork, communication, leadership, as well as personal and interpersonal skills. The study's objectives are to determine whether a teamwork framework can help to maintain academic integrity and transform BPM students into independent learners and leaders in the era of generative AI, and to determine whether lecturers' formative feedback enhances students' skills in teamwork assessment. This research comprises an empirical study of 408 local and international BPM students from different cultural backgrounds. A mixed-methods approach was used to collect data and achieve a broader perspective of the research topic. BPM students reported their satisfaction with this type of assessment since it helped them acquire skills such as intercultural effectiveness and teamwork. Following the implementation of the teamwork framework, the number of instances of academic misconduct and requests for extensions have decreased dramatically, while the assessment's average marks increased by 10 %. A set of recommendations is offered that will ensure the successful implementation of the proposed framework for teamwork assessment and self/peer evaluation. This study was limited to the Business Project Management unit, but in 2024, the same study will be conducted involving other postgraduate units at Curtin University with a future rollout in other universities to compare how students perceive teamwork assessment.